2023
DOI: 10.1186/s12883-023-03183-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of the language area in migraine: a preliminary classification model

Abstract: Background Migraine is a complex disorder characterized by debilitating headaches. Despite its prevalence, its pathophysiology remains unknown, with subsequent gaps in diagnosis and treatment. We combined machine learning with connectivity analysis and applied a whole-brain network approach to identify potential targets for migraine diagnosis and treatment. Methods Baseline anatomical T1 magnetic resonance imaging (MRI), resting-state functional MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Gou et al [17] examines MRI-based connectomes and found differences between the connectomes of patients with or without migraine. These studies suggest that connectomes are related to information processing in the neural network [18,19], differences in processing speed [20] and behaviour [21][22][23][24]; which can be collectively considered as "connectome basis of information processing".…”
Section: Introductionmentioning
confidence: 99%
“…Gou et al [17] examines MRI-based connectomes and found differences between the connectomes of patients with or without migraine. These studies suggest that connectomes are related to information processing in the neural network [18,19], differences in processing speed [20] and behaviour [21][22][23][24]; which can be collectively considered as "connectome basis of information processing".…”
Section: Introductionmentioning
confidence: 99%